The impact of the three-level digital divide on the mental health of rural residents: A study from China - Yi Ding; Yunhui Ai (PLoS ONE, 2026)
This study adopts the theoretical framework of “digital access divide—digital use divide—digital utility divide” to systematically investigate the differential impacts of different levels of the digital divide on the mental health of rural residents in China and its influencing mechanisms. Based on panel data from the China Family Panel Studies (CFPS) during 2020–2022, the study analyzes the internet access, usage, and perceived importance of rural residents in China, i.e., the situations of digital access divide, digital use divide, and digital utility divide they encounter, to examine the effects of these three levels of the digital divide on the mental health of rural residents.The findings are as follows: First, the digital access divide directly leads to a decline in mental health levels, and the digital use divide and digital utility divide, characterized by insufficient usage capabilities and improper usage behaviors, further exacerbate psychological damage. Second, different social groups exhibit heterogeneous results under the influence of the digital divide, with factors such as educational level and regional differences moderating the intensity of the digital divide’s impact. Third, there are hierarchical differences in the mechanisms of influence: The digital access divide reduces the mental health level of farmers by lowering their self-assessed sense of fairness. The digital use divide reduces the mental health level of farmers by lowering their self-assessed social class. The impact of the digital utility divide on the mental health of rural residents is achieved by reducing both self-assessed social class and self-assessed economic status. This study provides a new analytical perspective for understanding the mental health issues of rural residents in the context of digital technology popularization and has reference value for formulating precise digital inclusion policies.